Liturgical Architecture: Creating Space for Worship - Robinson, Gerald (Toronto journal of theology, 2012)
Space is a positive entity, capable of expression. It is the materiel of architecture. Rudolf Schwarz proposed six forms of space (the Six Plans) that would support Christian worship. I identify these six aspects of worship as contemplation, pastoral care, witness, dedication, evangelism, and justice. I give a functional analysis of each plan and an example of how it has been realized in practice. These plans create sacred spaces, each of which can support all the ministries of the Church.